Monitoring uterine activity during labor: a comparison of 3 methods - Euliano, Tammy Y.; Nguyen, Minh Tam; Darmanjian, Shalom; McGorray, Susan P.; Euliano, Neil; Onkala, Allison; Gregg, Anthony R. (American journal of obstetrics and gynecology, 2013)
Tocodynamometry (Toco; strain gauge technology) provides contraction frequency and approximate duration of labor contractions but suffers frequent signal dropout, necessitating repositioning by a nurse, and may fail in obese patients. The alternative invasive intrauterine pressure catheter (IUPC) is more reliable and adds contraction pressure information but requires ruptured membranes and introduces small risks of infection and abruption. Electrohysterography (EHG) reports the electrical activity of the uterus through electrodes placed on the maternal abdomen. This study compared all 3 methods of contraction detection simultaneously in laboring women. Upon consent, laboring women were monitored simultaneously with Toco, EHG, and IUPC. Contraction curves were generated in real-time for the EHG, and all 3 curves were stored electronically. A contraction detection algorithm was used to compare frequency and timing between methods. Seventy-three subjects were enrolled in the study; 14 were excluded due to hardware failure of 1 or more of the devices (n = 12) or inadequate data collection duration (n = 2). In comparison with the gold-standard IUPC, EHG performed significantly better than Toco with regard to the Contractions Consistency Index (CCI). The mean CCI for EHG was 0.88 ± 0.17 compared with 0.69 ± 0.27 for Toco (P < .0001). In contrast to Toco, EHG was not significantly affected by obesity. Toco does not correlate well with the gold-standard IUPC and fails more frequently in obese patients. EHG provides a reliable noninvasive alternative, regardless of body habitus.